PREPARATION AND EVALUATION OF SELF EMULSIFYING DRUG DELIVERY SYSTEM OF ROSUVASTATIN CALCIUM - AMIT VISHWAKARMA; MS NIMISHA; RICHA SRIVASTAVA; DIPTI SRIVASTAVA (International Journal of Pharma and Bio Sciences, 2016)
The objective of present research work was to develop a self emulsifying drug delivery system of Rosuvastatin Calcium for increasing its solubility, and oral bioavailability. Solubility of Rosuvastatin Calcium was determined in various vehicles. Oil, Surfactant and Cosurfactant were selected based on the solubility and HLB (Hydrophilic lipophilic balance) value.To identify the microemulsion existing zone Pseudo-ternary phase diagrams were constructed. Solubility analysis was also done for optimization of formulation. The optimized microemulsion formulation was evaluated for Powder X-Ray Diffraction (XRD), SEM (Scanning electron microscopy) analysis, globule size, zeta potential and phase separation study. Average globule size and zeta potential of the optimized microemulsion formulation were found to be 30 nm, and -11.5 mV, respectively. The viscosity and conductivity data indicated that the microemulsion was of the o/w type. Solubility of Rosuvastatin Calcium was successfully enhanced upto 82.32%. Percent drug release at the end of 60 mins was found to be 76.74 %. The solubility of Rosuvastatin Calcium was found to be significantly enhanced after formulating into self emulsifying microemulsion.